Technological Innovation in Marketing and its Effect on Consumer Behaviour - Suherlan, Suherlan; Okombo, Moses Odhiambo (Technology and Society Perspectives (TACIT), 2023)
In this modern era, the role of technology in marketing has undergone significant development along with advances in information and communication technology. Technological innovation has dramatically influenced companies' marketing strategies and has had a great impact on consumer behaviour. The purpose of this study is to investigate the relationship between technological innovation in marketing and how it affects consumer behaviour, with the aim of providing valuable insights for marketing practitioners and business researchers. The method used is a qualitative literature review that focuses on an in-depth understanding of the topic in the time span from 2001 to 2023. The main objective of this method is to identify, analyse, and synthesise relevant scientific literature that has been published in various journals, conference papers, and other academic sources accessible through Google Scholar. The results of this study have highlighted the important role of technology in changing the marketing landscape and consumer behaviour. In the ever-evolving digital age, such changes have a significant impact on the way companies interact with consumers, create value, and maintain their competitiveness.